Analiza občutljivosti toplotne obdelave jekel - Batista, Milan (Strojniški vestnik, 2000)
This paper presents a mathematical model of the heat treatment of hypoeutectoid carbon steel. In the model, the kinetics of phase changes and a thermo-elasto-plastic constitutive relation have been applied to calculate the residual stresses resulting from phase changes and temperature variation. The computer code has been verified for internal consistency with previously published results. The sensitivity analysis has been applied to predict errors in the residual stresses from the estimated errors in the material data.
Keywords: obdelave jekel; obdelave toplotne; analize občutljivosti; modeli matematični; toplotna obdelava; matematični modeli; jekla